Analisis Kemampuan Komunikasi Matematis Ditinjau dari Gaya Kognitif pada Siswa SMP-IT Yarsi Mataram - Bq. Nerik Prawita; Amrullah Amrullah; Nilza Humaira Salsabila; Laila Hayati (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to analyze the mathematical communication ability that is reviewed from the cognitive style on SMP-IT students of Yarsi in academic year 2021/2022. This study used descriptive method. The sample chosen by using nonprobability sampling technique with purposive sampling type, and the VIII Al-Farabi class is chosen as the sample. The subject selection technique in this research is based on the result of Group Embedded Figures Test (GEFT) consisted of 4 students. The instrument used is the essay test to acquire the data of students’ mathematic communication ability, while the Group Embedded Figures Test (GEFT) is used to determine the cognitive style and the interview from the students. From the research result, it is concluded that: (a) Students with Field Independent (FI) cognitive style have a good mathematic communication. The students in this stage are able to write and explain the mathematic idea logically and systematically, state the mathematical problem into drawing or table clearly and precisely, and also able to use the mathematical terms and symbols correctly. (b) Students with Field Dependent (FD) have the mathematic communication that is said to be not quite enough. The students in this stage are incapable to write and explain the mathematic idea logically and systematically, state the mathematical problem into drawing or table precisely and accurately, and also unable to use the mathematic terms and symbols correctly.